Mycelia Growth of Shiitake (Lentinula edodes) on 4-Wood Species from Leguminaceae Family - Dahayu Ratnanindha; Johanes Pramana Gentur Sutapa; Denny Irawati (Wood Research Journal, 2019)
Cultivation of  Shiitake  mushroom  (Lentinula edodes)  in  Indonesia has  not  been  developed  yet,  due  to  its  low productivity. It happens because of the limited information of the good ways on cultivation Shiitake in Indonesia. One of the factors that affect the growth of mushroom is the media. In Indonesia, the information about the media composition by using various species of wood have not been found yet. Therefore, this research was conducted to determine the effect of using different wood species to the growth of Shiitake. This study used four wood species from the leguminaceae family, those were: Gamal (Glicidia sepium); Johar (Samanea saman); Leucaena (Leucaena leucocephala); and Sengon (Falcataria moluccana). Those were used as the media by adding 12.5% (w/w) of rice bran and 6% (w/w) of CaCO3, and adjusting  the moisture content by adding the distillate water to 65, 70, and 75%. Then, the media was put in to the petridisk (ø 90 mm) and inoculated with Shiitake mushroom. During the mycelia growth, the length of mycelia was measured every 2 days until fifty days, and then glucosamine content was analyzed. In addition, chemical analysis was also conducted to each media. The results showed that different wood species resulted different chemical content of media, except the acid soluble lignin content. The growth rate of mycelia was affected by the moisture content of media, meanwhile the glucosamin content is influenced by the moisture content and various species of wood. The best combination to cultivate the Shiitake mushroom was by using media made of gamal with 70% moisture content. There were positive correlation among the ethanol-toluen extracts content and the mycelia growth, however there was negative correlation among the hemicelullose content the mycelia growth.